Masticatory performance in patients with jaw muscle pain: A case–control study - Al Sayegh, Samaa; Christidis, Nikolaos; Kumar, Abhishek; Svensson, Peter; Grigoriadis, Anastasios (Frontiers in Dental Medicine, 2022)
Introduction: Masticatory function is often impaired in patients with painful temporomandibular disorders (TMD) therefore more detailed studies on comminution and mixing ability are warranted in well-defined TMD patients with chronic myalgia. Moreover, there is a need to explore the correlation between any changes in perceived pain or fatigue in such patients and the masticatory function. Materials and Methods: Self-assessments using questionnaires regarding pain, oral health, jaw function, masticatory ability, fear of movement and psychosocial signs were answered by all the participants. A series of chewing tasks involving viscoelastic food and two-colored gum was performed. Optical imaging and analyzing was conducted. Bite force as well as characteristics of pain and fatigue were assessed. Results: In patients, the fragmented soft candy particles were less in number and had larger median of area and minimum Feret’s diameter after standardized chewing compared to healthy individuals (P = 0.02). Surprisingly, the two-colored Hue-Check gum was less mixed by the healthy controls since they displayed a greater variance of the hue (P = 0.04). There were significant differences between the patients and the healthy controls in the self-assessed masticatory ability mainly regarding pain-related variables. Conclusions: Objectively, TMD patients with chronic myalgia exhibited an impaired masticatory performance with less efficiency in comminuting soft viscoelastic food compared to the pain-free healthy control group. There was an agreement between the patients’ self-assessed masticatory ability and the efficiency of their masticatory function.